Foreign-born physicians' perceptions of discrimination and stress in Finland: a cross-sectional questionnaire study - Tarja Heponiemi; Laura Hietapakka; Salla Lehtoaro; Anna-Mari Aalto (BMC, 2018)
Abstract Background Foreign-born physicians fill in the shortage of physicians in many developed countries. Labour market theory and previous studies suggest that foreign-born physicians may be a disadvantaged group with a higher likelihood of discrimination and less prestigious jobs. The present study examines foreign-born physicians' experiences of discrimination (coming from management, colleagues and patients separately) and patient-related stress and integration-related stress, and it examines how gender, age, employment sector, country of birth, years from getting a practicing license in Finland, language problems, cross-cultural training, cross-cultural empathy, team climate and skill discretion were associated with these factors. Methods The present study was a cross-sectional questionnaire study among 371 foreign-born physicians in Finland, aged between 26 and 65 (65% women). Analyses of covariance and logistic regression analyses were conducted to examine the associations. Results A good team climate and high cross-cultural empathy were associated with lower likelihoods of discrimination from all sources, patient-related stress and integration-related stress. Skill discretion was associated with lower levels of integration-related stress and discrimination from management and colleagues. Language problems were associated with higher levels of integration-related stress. The biggest sources of discrimination were patients and their relatives. Conclusions The present study showed the importance of a good team climate, cross-cultural empathy and patience, skill discretion and language skills in regard to the proper integration of foreign-born health care employees into the workplace. Good job resources, such as a good team climate and the possibility to use one's skills, may help foreign-born employees, for instance by giving them support when needed and offering flexibility. Health care organizations should invest in continuous language training for foreign-born employees and also offer support when there are language problems. Moreover, it seems that training increasing cross-cultural empathy and patience might be beneficial.